THE COMPONENTS OF INTELLECTUAL CAPITAL THAT AFFECT FIRM PERFORMANCE IN STATE-OWNED COMPANIES - Debbie Setiady1; Yanti, Yanti; Sastrasasmita, Emillia (Graduate Program of Universitas Tarumanagara, 2023)
The purpose of this study is to examine the effect of independent variables of human capital efficiency (HCE), capital employed efficiency (CEE), and structural capital efficiency (SCE) on firm performance. This study uses firm size as a control variable. The sample in this study was selected using purposive sampling which resulted in 11 state-owned companies from 12 companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2022 period were used as research objects. This study uses a panel data regression model with a Common Effect Model (CEM) approach using Eviews version 12 program. Based on the analysis, the results of this study shows that human capital efficiency (HCE), capital employed efficiency (CEE) and firm size have a positive and significant effect on firm performance, while structural capital employed (SCE) have an insignificant effect on firm performance. These findings also revealed that companies that can manage their assets including intangible assets will improve company performance.